Culprit versus multivessel coronary intervention in ST-segment elevation myocardial infarction: a meta-analysis of randomized trials. Issue 2 (March 2018) - Vaidya, Satyanarayana R.; Qamar, Arman; Arora, Sameer; Devarapally, Santhosh R.; Kondur, Ashok; Kaul, Prashant
Abstract : Background: The 2015 American College of Cardiology/American Heart Association update on primary percutaneous coronary intervention (PCI) in patients with ST-segment elevation myocardial infarction (STEMI) recommended PCI of the non-infarct-related artery at the time of primary PCI (class IIb recommendation). Despite evidence supporting complete revascularization in STEMI, its benefit on mortality rates is uncertain. Methods: We searched all available databases for randomized controlled trials comparing complete multivessel percutaneous coronary intervention (CMV PCI) with infarct-artery-only revascularization in patients with STEMI. Summary risk ratios and 95% confidence intervals (CIs) were calculated for both the efficacy and safety outcomes. Results: Nine randomized controlled trials fulfilled the inclusion criteria, yielding 2991 patients. Follow-up periods ranged from 6 to 36 months. Compared with infarct-related artery-only PCI, CMV PCI was associated with significantly lower rates of major adverse cardiac events [relative risk (RR)=0.54, 95% CI=0.41–0.71; P <0.00001], cardiovascular mortality (RR=0.48, 95% CI=0.28–0.80; P =0.005), and repeat revascularization (RR=0.38, 95% CI=0.30–0.47; P <0.00001). Although, contrast-induced nephropathy and major bleed rates were comparable between both groups, CMV PCI failed to show any reduction in all-cause mortality (RR=0.75, 95% CI=0.53–1.07; P =0.11) and nonfatal myocardial infarction (RR=0.69, 95% CI=0.43–1.10; P =0.12). Conclusion: Our results suggest that in patients with STEMI and multivessel disease, complete revascularization is safe, and is associated with reduced risks of major adverse cardiac events and cardiac death along with a reduced need for repeat revascularization. However, it showed no beneficial effect on all-cause mortality and nonfatal myocardial infarction. Abstract : Supplemental Digital Content is available in the text.